Site‐Specific SERS Assay for Survivin Protein Dimer: From Ensemble Experiments to Correlative Single‐Particle Imaging. Issue 32 (4th July 2017) - Wissler, Jörg; Bäcker, Sandra; Feis, Alessandro; Knauer, Shirley K.; Schlücker, Sebastian
Abstract : An assay for Survivin, a small dimeric protein which functions as modulator of apoptosis and cell division and serves as a promising diagnostic biomarker for different types of cancer, is presented. The assay is based on switching on surface‐enhanced Raman scattering (SERS) upon incubation of the Survivin protein dimer with Raman reporter‐labeled gold nanoparticles (AuNP). Site‐specificity is achieved by complexation of nickel‐chelated N ‐nitrilo‐triacetic acid (Ni‐NTA) anchors on the particle surface by multiple histidines (His6 ‐tag) attached to each C‐terminus of the centrosymmetric protein dimer. Correlative single‐particle analysis using light sheet laser microscopy enables the simultaneous observation of both elastic and inelastic light scattering from the same sample volume. Thereby, the SERS‐inactive AuNP‐protein monomers can be directly discriminated from the SERS‐active AuNP‐protein dimers/oligomers. This information, i.e. the percentage of SERS‐active AuNP in colloidal suspension, is not accessible from conventional SERS experiments due to ensemble averaging. The presented correlative single‐particle approach paves the way for quantitative site‐specific SERS assays in which site‐specific protein recognition by small chemical and in particular supramolecular ligands can be tested. Abstract : An assay for Survivin protein dimers, based on surface‐enhanced Raman scattering (SERS) of Raman reporter‐ and Ni‐NTA‐functionalized gold nanoparticles, is presented. The formation of gold nanoparticle dimers and small oligomers upon site‐specific binding of the protein to the gold nanoparticles is probed by ensemble SERS measurements and correlative single‐particle imaging.